PERBANKAN SYARIAH DALAM PERSPEKTIF DIGITALISASI (TRANSFORMASI, PRODUK DAN TEKNOLOGI) - Eni Haryani Bahri; Rizka Ar Rahmah; Satria Darma (HUMAN FALAH: Jurnal Ekonomi Dan Bisnis Islam, 2026)
Digital transformation presents opportunities and challenges for the business and financial industries. Islamic banking is expected to accelerate the development of digital technology. This study aims to determine how Islamic banking maintains Sharia principles while adapting to technological dynamics in the context of digitalization. The research method applied in this study is a descriptive analytical method utilizing secondary data. The reason for this is to examine issues in the social, economic, or policy fields, as it uses data that has been previously collected and published, thereby saving time and costs. The results of the study show that by issuing Financial Services Authority Regulation (POJK) No. 77/POJK.01/2016 on information technology-based money lending services, Bank Indonesia and the Financial Services Authority have established clear and firm provisions that protect the interests of the public, both as lenders and borrowers. Bank Indonesia then issued Governor Board Regulation No. 19/14/PADG/2017 on Financial Technology (Regulatory Sandbox) as a limited testing area that is safe from a regulatory perspective. Testing of financial technology providers along with their goods, services, technology, and/or business plans is known as a limited testing area.